L’immigration polonaise et la colonisation du Sud du Brésil - Márcio de Oliveira (Cahiers des Amériques Latines)
This article aims to analyze the importance of Polish immigration for the colonization of southern Brazil. After presenting the main trends of the immigration in Brazil, we discuss the immigration policies of the State of Brazil, and particularly of the state of Paraná between 1870 and 1914. It’s realized that there are very few studies about groups of immigrants like the Ukrainians or the Polishes. For the last ones, we reveal their history since their departure from Europe until their arrival in Brazil and their migration to the state of Paraná. We conclude with a discussion about the role of the Polish immigrants – that can be seen both as a rural colon and as a conqueror – in southern Brazil.